2010
DOI: 10.1007/s10800-010-0166-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and modeling of the electrodialytic and dialytic treatment of a fly ash containing Cd, Cu and Pb

Abstract: A one-dimensional model is developed for simulating the electrodialytic and dialytic treatment of a fly ash containing cadmium, copper and lead. Two experimental systems have been used, a column of ash and a stirred ash suspension. The movement of Cd, Cu and Pb has been modeled taking into account the diffusion transport resulting from the concentration gradients of their compounds through the membranes and boundary layers and the electromigration of their ionic, simple and complex species during the operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
(18 reference statements)
1
3
0
Order By: Relevance
“…This might occur because MSWI fly ash has a large number of carbonate ions which react with hydrogen ions and release CO 2 . Similar phenomenon was observed by [ 29 ].…”
Section: Resultssupporting
confidence: 91%
“…This might occur because MSWI fly ash has a large number of carbonate ions which react with hydrogen ions and release CO 2 . Similar phenomenon was observed by [ 29 ].…”
Section: Resultssupporting
confidence: 91%
“…Under this framework, several researchers have reported on the electrodialytic (ED) treatment of fly ash and APC residue at laboratory and pilot scale, targeting the successful removal of heavy metals and soluble salts and the valorization of these wastes [8][9][10][11][12][13][14][15]. Even though this technique has shown great potential, no studies so far have reported its effect on the PCDD/PCDF content in fly ash and APC residue, and this missing information is crucial to properly assess possible valorization options.…”
Section: Introductionmentioning
confidence: 99%
“…Further developments include the electrodialytic and dialytic treatment of a fly ash [42], and also the electrokinetic desalination treatments [43].…”
Section: Introductionmentioning
confidence: 99%